2022
DOI: 10.3389/fpls.2022.1087378
|View full text |Cite
|
Sign up to set email alerts
|

The coordinated regulation mechanism of rice plant architecture and its tolerance to stress

Abstract: Rice plant architecture and stress tolerance have historically been primary concerns for rice breeders. The “Green Revolution” and super-rice breeding practices have demonstrated that ideal plant architecture can effectively improve both stress tolerance and yield. The synergistic selection and breeding of rice varieties with ideal architecture and stress tolerance can increase and stabilize yield. While rice plant plant architecture and stress tolerance are separately regulated by complicated genetic networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Using miRNA-mRNA integration analysis, recent investigations have broadened our knowledge of how plants respond to stress 14 , 39 , 42 , 51 . This current study identified several miRNA-target gene pairs that respond to salt stress and developed a regulatory network using DEMIs and DEMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using miRNA-mRNA integration analysis, recent investigations have broadened our knowledge of how plants respond to stress 14 , 39 , 42 , 51 . This current study identified several miRNA-target gene pairs that respond to salt stress and developed a regulatory network using DEMIs and DEMs.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important in transcriptome studies of species where genomic information is relatively limited 11 . Transcriptome sequencing approaches have been widely applied in agriculture, including the exploration of resistance genes in animals and plants 12 , 13 , the study of resistance 14 , and metabolic mechanisms 15 .…”
Section: Introductionmentioning
confidence: 99%